2010
DOI: 10.1002/mnfr.201000045
|View full text |Cite
|
Sign up to set email alerts
|

Hydro‐ethanolic extract of cashew tree (Anacardium occidentale) nut and its principal compound, anacardic acid, stimulate glucose uptake in C2C12 muscle cells

Abstract: Activation of adenosine monophosphate-activated protein kinase by CSE and AA likely increases plasma membrane glucose transporters, resulting in elevated glucose uptake. In addition, the dysfunction of mitochondrial oxidative phosphorylation may enhance glycolysis and contribute to increased glucose uptake. These results collectively suggest that CSE may be a potential anti-diabetic nutraceutical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 35 publications
2
28
0
1
Order By: Relevance
“…The ability of tree nuts to improve glycemic control may relate to activation of adenosine monophosphate-activated protein kinase in C2C12 myotubes as we demonstrated [1]. Our results are in line with a recent meta-analysis of randomized controlled dietary trials supporting the effect of tree nut on glycemic control in diabetes [15].…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The ability of tree nuts to improve glycemic control may relate to activation of adenosine monophosphate-activated protein kinase in C2C12 myotubes as we demonstrated [1]. Our results are in line with a recent meta-analysis of randomized controlled dietary trials supporting the effect of tree nut on glycemic control in diabetes [15].…”
Section: Resultssupporting
confidence: 90%
“…In our previous studies, we found that hydro-ethanolic extract of cashew seed (CSE), stimulated glucose transport in C2C12 myotubes [1].…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…80 Anacardic acid, which is present in cashew nuts, can inhibit several HATs, including PCAF, Tip60 and p300; 81 in addition, anacardic acid can also promote glucose uptake by myotubes through the activation of AMP-activated protein kinase (AMPK) and uncouple rat liver mitochondria, thus potentially contributing to enhanced glycolysis and glucose uptake. 81 Curcumin, the active compound of Curcuma longa (turmeric), a plant of the ginger family, has caught attention as a potential epidrug for diabetes, given its hypoglycemic, hypolipidemic, and epigenetic effects in various rodent models. 82 Curcumin has DNA hypomethylating activity and influences both histone acetylation and miRNA expression.…”
Section: Histone Acetyltransferase Inhibitorsmentioning
confidence: 99%
“…O caju apresenta características importantes do ponto de vista nutricional, contendo cerca de 156 a 378 mg de vitamina C, 14,70 mg de cálcio, 32,55 mg de fósforo e 0,57 mg de ferro, por 100 mL de suco (EMBRAPA, 2004). Possui também elevadas concentrações de polifenóis, como ácidos anacárdicos (TEDONG et al, 2010;OLIVEIRA et al, 2012), que estão sendo pesquisados por envolvimento na prevenção de distúrbios, como câncer, dano oxidativo, inflamação e obesidade (HEMSHEKHAR et al, 2012).…”
Section: Introductionunclassified